UAV collision detection algorithm design based on circle overlapping test - Radzi, N.F.M.; Mubin, M.; Rahim, N.A.; Mokhtar, N. (2012)
Each UAV require a robust collision detection in its operating system to ensure it can aware the potential of collision in near future. Collision detection algorithm is one of the important parts that need to be concerned in the CAS. This paper proposes a design of collision avoidance algorithm for unmanned aerial vehicle based on circle overlapping test. Assuming two moving UAV are flying in the same altitude and in straight path within a two dimensional plane as conflict problem. Both UAV are cooperative aircrafts which communication of position, heading angle, waypoint, and velocity are allowed. The proposed algorithm will determine the collision potential between the surrounding intruders according to the conflict information.